Different derivations of the Shalstab model as a tool to monitor the susceptibility of mass movements in watersheds with the present of energy transmission assets - Gerente, Jéssica; Luiz , Edna Lindaura; Gomes Junior , Francisco Caruso; Providelo , Lucas Antônio; Marchiori , Guilherme (Revista do Departamento de Geografia, 2023)
The objective of this work is to evaluate the use of the Shalstab model to make a diagnosis of the susceptibility of mass movements considering three different approaches: i) Shalstab at risk level (log reason result (q/t)) pixel by pixel; ii) Shalstab at generalized risk level by basins; iii) Daily critical rain required for burst blackout (Shalstab in terms of “q” - precipitation). The study area refers to hydrographic basins that intersect a transmission line located in the Serra do Mar Paranaense and for the parameterization of the geotechnical values ​​used in the modeling, a spatialized approach was adopted. This approach that takes into account the variability of the geological typology of the area. The mass movement scars used to validate the results indicate that both approaches of the model at risk level (pixel by pixel and generalized by basin) were able to identify the most susceptible areas with a good level of accuracy. Regarding the critical rain in the study area, precipitations above 100mm/day are dangerous for many locations. This value of precipitation is quite common in the region, which indicates the need for attention, especially at times with rainfall configurations close to this threshold.